1986
DOI: 10.1002/1097-0142(19860601)57:11<2135::aid-cncr2820571109>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistologic identification of phenotypic antigens associated with Hodgkin and reed-sternberg cells. A paraffin section study

Abstract: A combination of two monoclonal antibodies, designated LN-1 and LN-2, were used in an attempt to identify the corresponding antigens in Hodgkin and Reed-Sternberg cells. The LN-1 antibody has been shown in previous studies in our laboratories to identify follicular center cells, whereas LN-2 marks certain B-cell subpopulations as well as interfollicular histiocytes. Utilizing the perioxidase-antipenoxidase (PAP) technique, paraffin-embedded sections were examined representing 39 cases of various histologic sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…There is little variance from recent reports concerning the percentage of positive staining with anti-CD15 antibodies, although smaller (Ree et al, 1989) and larger percentages of (Chittal et al, 1988;Dorfman et al, 1986; positive cases have been reported. Differences are also reported with the monoclonal antibodies Ber-H2 (Chittal et al, 1988;Ree et al, 1989;Schwarting et al, 1989), especially in the mixed cellularity type (Hall et al, 1988), and LN-2 (Sherrod et al, 1986;Chittal et al, 1988;Ree et al, 1989). The discordant results among different authors may result from technical differences or depend in part on the small numbers of cases examined (Sherrod et al, 1986;Hall et al, 1988).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…There is little variance from recent reports concerning the percentage of positive staining with anti-CD15 antibodies, although smaller (Ree et al, 1989) and larger percentages of (Chittal et al, 1988;Dorfman et al, 1986; positive cases have been reported. Differences are also reported with the monoclonal antibodies Ber-H2 (Chittal et al, 1988;Ree et al, 1989;Schwarting et al, 1989), especially in the mixed cellularity type (Hall et al, 1988), and LN-2 (Sherrod et al, 1986;Chittal et al, 1988;Ree et al, 1989). The discordant results among different authors may result from technical differences or depend in part on the small numbers of cases examined (Sherrod et al, 1986;Hall et al, 1988).…”
Section: Discussionsupporting
confidence: 55%
“…Differences are also reported with the monoclonal antibodies Ber-H2 (Chittal et al, 1988;Ree et al, 1989;Schwarting et al, 1989), especially in the mixed cellularity type (Hall et al, 1988), and LN-2 (Sherrod et al, 1986;Chittal et al, 1988;Ree et al, 1989). The discordant results among different authors may result from technical differences or depend in part on the small numbers of cases examined (Sherrod et al, 1986;Hall et al, 1988). Apart from the three antibodies mentioned above, the lectin peanut agglutinin has proved a useful marker for RSC and HC (Moller, 1982;Ree et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lesions in cutaneou5 Hodgkin's disease are often papular or nodular and may progress to ulcerate similar to transformed CTCL; however, cutaneous Hodgkin's disease is usually seen in proximity to pathologic adenopathy (Smith and Butler, 1980). Expression of the markers LeuM 1, Ki-1, and LN2 may be found in RS cells and transformed T cells, but the use of LCA and UCHLl may allow differentiation of these two processes in most cases (Pinkus et al, 1985;Linden et al, 1987;Hsu and Jaffe, 1984;Sherrod et al, 1986;Hsu et al, 1985;Casey et al, 1986b). In both of our cases with coexistent transformed CTCL and Hodgkin's disease, large transformed T cells reacted with both UCHL 1 and LCA while RS cells were negative.…”
Section: Discussionmentioning
confidence: 99%
“…When adequate samples were available, the phenotype of Reed-Sternberg cells and background lymphocytes was determined with standard immunoperoxidase techniques. 20 Specimens from the pairs of twins concordant for disease were evaluated for evidence of EBV with the polymerase chain reaction to detect viral DNA sequences (with primers SL1 5 Ј GGACCTCAAAGAAGAGGGGG and SL3 GCTCCTGGTCTTCCGCCTCC and a probe specific for EBV nuclear antigen 1, SL2 GGACGAGGACGGGGAAGAGG), or by a method that is at least as sensitive, in situ hybridization (with a 30base sequence, 5 Ј AGACACCGTCCTCACCACCCGGGACTTGT-A3 Ј , complementary to a portion of the EBER-1 gene that is actively transcribed in latently infected cells). 7 In some cases both methods were used.…”
Section: Assessment Of Pairs Concordant For Hodgkin's Diseasementioning
confidence: 99%